Artificial Neural Networks and Machine Learning -- ICANN 2013 23rd International Conference on Artificial Neural Networks, Sofia, Bulgaria, September 10-13, 2013, Proceedings - Mladenov, Valeri; Koprinkova-Hristova, Petia; Palm, Günther; Villa, Alessandro; Apolloni, Bruno; Kasabov, Nikola K. (Theoretical Computer Science and General Issues, 2013)
The book constitutes the proceedings of the 23rd International Conference on Artificial Neural Networks, ICANN 2013, held in Sofia, Bulgaria, in September 2013. The 78 papers included in the proceedings were carefully reviewed and selected from 128 submissions. The focus of the papers is on following topics:neurofinance graphical network models, brain machine interfaces, evolutionary neural networks, neurodynamics, complex systems, neuroinformatics, neuroengineering, hybrid systems, computational biology, neural hardware, bioinspired embedded systems, and collective intelligence.